DIFFERENCES IN COMPUTER-TOMOGRAPHIC SIZE OF PREMOLAR TEETH AND THEIR ROOTS IN PRACTICALLY HEALTHY MEN OF DIFFERENT CRANIOTYPES, INHABITANTS OF THE CENTRAL REGION OF UKRAINE - Shinkaruk-Dykovytska, М.М.; Orlovskiy, V.О.; Gavrilyuk, А.О.; Datsenko, G.V.; Zakalata, T.R. (World of Medicine and Biology, 2017)
In practically healthy men of the central region of Ukraine, the largest number of statistically significant or tendencies to differences in the linear computational-tomographic size of premolar teeth and their roots was established by comparing dolichocephals and mesocephals with brachycephals and hyperbrachycephals. Brachycephals and hyperbrachycephals show the highest values of both vertical and transverse sizes of premolar teeth compared to those of other craniotypes (mainly due to the vestibule-lingual and mesiodistal dimensions of the crown and neck of the tooth). Between men dolichocephals and mesocephals, in general, no statistically significant or tendency differences of computer-tomographic size of premolar teeth and their roots were found.
Keywords: premolar teeth; computer tomography; practically healthy men; craniotypological features; central region of Ukraine